Sense of purpose in life and motivation, barriers, and engagement in physical activity and sedentary behavior: Test of a mediational model. (August 2022) - Sutin, Angelina R; Luchetti, Martina; Stephan, Yannick; Terracciano, Antonio
Purpose in life is associated with greater engagement in physical activity. The present research ( N = 3473) addresses whether motivations and barriers to physical activity mediate this relation concurrently and prospectively early in the coronavirus pandemic. Higher purpose was associated with greater intrinsic, identified, and external motivation for physical activity and fewer barriers. Intrinsic motivation was a robust mediator of the relation between purpose and more physical activity and less sedentary behavior reported concurrently and prospectively; identified motivation mediated the relation with physical activity. Purpose in life is associated with being more physically active through both greater enjoyment and valuing its benefits.